Health Promotion of Children of School Age with the Help of Physical Education on the Basis of State of Health (Eurasian Scientific Herald, 2022)
This article provides a comprehensive coverage of improving the health status of school-age children using physical education tools. Also, the indicators of the control of the physical abilities of schoolchildren-girls were analyzed